Conhecimentos da Terapia Ocupacional no Brasil : um estudo sobre trajetórias e produções - Cardinalli, Isadora (Universidade Federal de São Carlos, 2016)
This work aims at the production of knowledge about Occupational Therapy in Brazil. This subject is explored by means of the current view of the scientific profile and the historical course of the profession from written and oral sources, reflecting on knowledge, conceptions and perspectives produced by occupational therapists up to the present time, including external and internal forces that make up the production of knowledge and action fields. The objective of this research is to understand the processes of production of knowledge about Brazilian Occupational Therapy by means of professional trajectories, theoretical and methodological production, conceptions and perspectives. It is about an exploratory research of a subject that is supposed to be revised nowadays with a qualitative and participant approach bringing the participants to the dialogue and composition of the text. Plural methodological procedures, articulated and compound, have been included at the presentation of results. Researchers who invest on general subjects of the Brazilian Occupational Therapy have been identified through a mapping process. Two identified researchers and three occupational therapists indicated by them are the interlocutors of this work, because of their production of dialogues about Brazilian Occupational Therapy in a comprehensive way. These interlocutors have been interviewed to get to know their trajectories, conceptions, perspectives and production about Occupational Therapy. Historical routes, challenges about the profession in Brazil, their construction of knowledge and debate on identity have been presented. It reflects about fundamentals, epistemology and theoretical and methodological perspectives, objects of study, concepts, conceptions and knowledge of Occupational Therapy in Brazil along history and at the present time. The aim is to value the diversity of expressions, stories and the interlocutors' individual production as well as to relate to their trajectories and experiences in knowledge production, which currently contribute for the composition of the net of knowledge about the profession. By means of their individual trajectory and its context, it is possible to find connections and instigating components for knowledge production about the profession. By gathering action fields, knowledge areas, references, support nets and other interlocutors, it has been possible to map part of the composition of the net of knowledge production of the profession at the present time. Some changes and transformation have been observed in the way of conceiving a profession, of acting and producing knowledge which influences on the national identity of Occupational Therapy and its epistemologic construction. It has been possible to explore the field, make up stories, memories, trajectories and reflect on produced knowledge about the profession in Brazil, thus, conceiving history and memory as collective and social constructions, identifying this way, producers and interlocutors of this knowledge and outstanding connection points in their trajectory, valuing knowledge production about Brazilian Occupational Therapy, and contributing for a discussion around general knowledge about the profession, its fundamentals, epistemology, identity, concepts, conceptions and perspectives, theoretical and methodological, in the Brazilian and contemporary context.
Keywords: Terapia Ocupacional brasileira; Produção de conhecimentos; História; Epistemologia; Brazilian Occupational Therapy; Knowledge production; History; Epistemology; OUTROS